The Role of Intangible Assets of Scientific Research Human Resources - Ha, Mai; Van Hoa, Nguyen (VNU Journal of Science: Policy and Management Studies, 2021)
The article provides analysis of the scientific concepts and contents related to the intangible assets of scientific research human resources. With scientific arguments, the author gives his views to the important role of intangible assets of science and technology human resources in general and scientific research human resources in particular. In the process of designing policies for development of science and technology human resource, policy makers should take into account the intangible assets of scientific research human resources to create an adequate environment for scientific creative labor and to provide right assessments of the value of creative work in research and development activities. Keywords Intangible asset, scientific research, development policy, scientific creative work, scientific research human resource, innovation. References [1] M. Ha, H.V. Tuyen, D.T. Truong, Science and Technology Enterprises: From the Theory to Practice, ISBN 978-604-67-0481-2, Science and Technics Publishing House, Ha Noi, Vietnam, 2015 (in Vietnamese) [2] M. Ha, Innovation and Scientificiy of the term “innovation” in the sence of “innovation” in policy research in Vietnam The Sc. Journal of Sociology. ISSN 2615-9163, 3 (147) (2019) 3-10 (in Vietnamese). [3] OECD, Guidelines for Collecting and Reporting Data on Research and Experimental Development, Frascati Manual, 2005. [4] M. Ha, Specific Particularities of S&T Research Labor Sc. Journal of S&T Policy and Management, ISSN 1859-3801, 1(1) (2011) 4-10 (in Vietnamese). [5] M. Ha (Key Editor), Q&A on Industrialization and Modelization, Youth Publishing House, Ha Noi, 1997 (in Vietnamese), [6] M. Ha, The Role of Intelligensia in Economic Development and International Integration (in Vietnamese). Journal of Science: Policy and Management Studies. ISSN 0866-8612, 31(1) (2015).